The covalent reactivity of functionalized 5-hydroxy-butyrolactams is the basis for targeting of fatty acid binding protein 5 (FABP5) by the neurotrophic agent MT-21. Issue 10 (14th September 2022) - Svenningsen, Esben B.; Ottosen, Rasmus N.; Jørgensen, Katrine H.; Nisavic, Marija; Larsen, Camilla K.; Hansen, Bente K.; Wang, Yong; Lindorff-Larsen, Kresten; Tørring, Thomas; Hacker, Stephan M.; Palmfeldt, Johan; Poulsen, Thomas B.
Abstract : In this work, it is shown that an N -acyl hemiaminal motif present in many natural products can function as an electrophilic centre, mediating covalent reactivity in biological systems, reacting with both thiols and amines. Abstract : Covalently acting compounds experience a strong interest within chemical biology both as molecular probes in studies of fundamental biological mechanisms and/or as novel drug candidates. In this context, the identification of new classes of reactive groups is particularly important as these can expose novel reactivity modes and, consequently, expand the ligandable proteome. Here, we investigated the electrophilic reactivity of the 3-acyl-5-hydroxy-1, 5-dihydro-2 H -pyrrole-2-one (AHPO) scaffold, a heterocyclic motif that is e.g. present in various bioactive natural products. Our investigations were focused on the compound MT-21 – a simplified structural analogue of the natural product epolactaene – which is known to have both neurotrophic activity and ability to trigger apoptotic cell death. We found that the central N -acyl hemiaminal group of MT-21 can function as an electrophilic centre enabling divergent reactivity with both amine- and thiol-based nucleophiles, which furthermore translated to reactivity with proteins in both cell lysates and live cells. We found that in live cells MT-21 strongly engaged the lipid transport protein fatty acid-binding protein 5 (FABP5) by direct binding to a cysteine residue in the bottom of the ligand binding pocket. Through preparation of a series of MT-21 derivatives, we probed the specificity of this interaction which was found to be strongly dependent on subtle structural changes. Our study suggests that MT-21 may be employed as a tool compound in future studies of the biology of FABP5, which remains incompletely understood. Furthermore, our study has also made clear that other natural products containing the AHPO-motif may likewise possess covalent reactivity and that this property may underlie their biological activity.